MANAJEMEN LAYANAN PRIMA BERBASIS NILAI-NILAI ISLAM DALAM PELAYANAN PENDIDIKAN DIPONDOK PESANTREN AR-RAHMAN PETAPAHAN - Nasyilla Aulia; Aulia; Saskia Wanda Audiya; Dea Fitri Rahmadani; Nurvia Dewi Pusvita; Desniati; Rani Sania; Adwa Syifa Aulia; Irawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the implementation of excellent service management based on Islamic values in educational services at Ar-Rahmah Petapahan Islamic Boarding School. Excellent service is an important element in managing educational institutions as it is closely related to efforts to meet the needs, expectations, and satisfaction of educational service users. In the boarding school environment, educational services are not only focused on administrative and academic aspects but also emphasize Islamic values as the foundation for providing services to students, parents, and the community. Islamic values such as honesty, trustworthiness (amanah), responsibility, discipline, sincerity, patience, and mutual respect serve as guidelines in every service process carried out by the institution. This research employed a qualitative approach using a case study method. Data were collected through observation, in-depth interviews, and documentation. The research participants consisted of the boarding school leader, teaching staff, administrative staff, students, and parents who were directly involved in the educational service process. The collected data were analyzed through data reduction, data presentation, and conclusion drawing to obtain a comprehensive understanding of the implementation of excellent service management based on Islamic values at Ar-Rahmah Petapahan Islamic Boarding School. The findings indicate that excellent service management has been implemented through various forms of service that prioritize friendliness, politeness, responsiveness, discipline, transparency, and accountability. The application of Islamic values is reflected in the interactions among teachers, administrative staff, students, and parents, which are guided by the principles of akhlaqul karimah (noble character). Furthermore, the boarding school strives to provide services that are fast, accurate, and fair, thereby creating a conducive educational environment that supports the learning process. The implementation of excellent service management based on Islamic values not only improves the quality of educational services but also strengthens public trust in the institution and supports the development of students with noble character. Based on the research findings, it can be concluded that excellent service management grounded in Islamic values plays a significant role in enhancing the effectiveness of educational services, strengthening relationships between the boarding school and its stakeholders, and supporting the achievement of Islamic educational goals oriented toward knowledge development, character building, and the reinforcement of Islamic values in daily life. Keywords: Excellent Service Management, Islamic Values, Educational Services, Islamic Boarding School, Service Quality